42-Year-Old Patient With Severe COVID-19 Pneumonia and Cytokine Storm: Hurdles During Management (Journal of Medicine, 2020)
A middle aged man presented with fever for 14 days, dry cough for 10 days and shortness of breath for 6 days. He tested positive for RT-PCR for COVID-19 on 5th day of illness. Patient was maintaining home isolation until he developed shortness of breath. After hospitalization patient was treated with standard dose of Remdesivir, dexamethasone and antibiotics. But his oxygen demand was increasing day by day. Inflammatory markers including serum ferritin, CRP level was also increasing. Patient was having a cytokine storm. At this point of treatment anti IL6 Tocilizumab was being considered. But patient’s wellbeing was improved and tocilizumab was not given. Our patient gradually recovered from severe COVID-19 pneumonia and cytokine storm without tocilizumab.J MEDICINE JUL 2020; 21 (2) : 119-122